Is there a Brazilian model of development? Are there lessons for countries in Africa? - Ed Amann; Armando Barrientos (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
Brazil's recent growth has been intensely pro-poor, and both poverty and inequality have declined significantly in the last decade. It has been suggested that Brazil's unexpected successes are the outcome of a new model of development. The paper argues that Brazil's unique combination of economic and social policies is at the root of its inclusive growth, but it is poorly understood. An assessment as to whether this combination constitutes a model is perhaps premature, but it is worth considering whether there are any lessons from Brazil's development policies for Sub-Saharan African countries.
Keywords: O1; O5; I3; 330; Brazil; inclusive growth; development; poverty